Neurological safety and efficacy of darifenacin and mirabegron for the treatment of overactive bladder in patients with history of cerebrovascular accident: A prospective study. Issue 8 (13th September 2021) - Vasudeva, Pawan; Kumar, Amitabh; Yadav, Siddharth; Kumar, Niraj; Chaudhry, Neera; Prasad, Vishnu; Nagendra Rao, Swatantra; Yadav, Prashant; Patel, Samarth
Abstract: Objectives: To evaluate the neurological safety and clinical efficacy of darifenacin and mirabegron in patients with a history of cerebrovascular accident (CVA) who had overactive bladder (OAB) symptoms. Methods: This prospective randomized study, approved by the institute's ethics committee, was carried out at a tertiary care center from December 2018 to June 2020. Treatment naïve adult patients with a past history of CVA with stable neurological status for atleast past 3 months with symptoms of OAB for 3 or more months were included. Eligible patients received either darifenacin or mirabegron for a period of 3 months and various parameters on the 3‐day International Consultation on Incontinence Questionnaire (ICIQ) bladder diary, the Montreal Cognitive Assessment—Basic score (MoCA‐B), and the adverse events at 3 months posttreatment were compared to that at the baseline. Results: A total of 60 patients were included, 30 in each arm. After 3 months of treatment with darifenacin or mirabegron, the majority of the ICIQ bladder diary parameters improved and there was no deterioration in the cognitive function as noted on the MoCA‐B score in either of the arms. On intergroup comparison, the mean change in bladder diary parameters and the MoCA‐B scores was similar between the two groups. Conclusion: Darifenacin and mirabegron, in the short term, do not adversely affect the cognitive function in patients with a history of CVA with OAB symptoms. Both are safe and effective treatment options in patients with OAB post‐CVA.